A folklore tradition on the fall of Srebrenik under the Ottoman rule and historical imagination of the mid-19th century - Rabić, Nedim (Historical Thought, 2025)
The subject of this paper are the diary notes of the Bavarian botanist Otto Sendtner published in the German magazine "Das Ausland" regarding the medieval fortress of Srebrenik and the tradition about its fall under the Ottoman rule, which were completely unknown in the literature. This Munich university professor stayed in the Bosnian ejalet/Province in 1847, and on that occasion, he visited a significant number of cities, starting with Split, Livno and Travnik as the main destination. From the vizier’s city and the seat of Ejalet, he went to Bosanska Posavina due to his botanical research, and on that occasion he passed through Srebrenik. Sendtner wrote in detail about the fortress, inspired by its features, and also left a note of local folklore tradition regarding its fall under the Ottomans, which deserves special attention. Also, in Sendtner’s exposition, romantic narratives and orientalism ele-ments can be observed in the descriptions of the Srebrenik fortress and the landscape surrounding it, which can be attributed to the features of the imagination about the Middle Ages presented in the European intellectual circles during the middle of the 19th century.